1994
DOI: 10.1001/archpsyc.1994.03950020040004
|View full text |Cite
|
Sign up to set email alerts
|

Striatal D2 Dopamine Receptor Characteristics in Neuroleptic-Naive Schizophrenic Patients Studied With Positron Emission Tomography

Abstract: There are no general changes in D2 dopamine receptor Bmax or Kd values in neuroleptic-naive schizophrenics, but there may be a subgroup of patients with aberrant striatal D2 dopamine receptor characteristics in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(76 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…The binding characteristics of some of the subjects have been previously published. 2,29,30 The subjects were clinically examined and were found to be free of psychiatric and neurologic disorders. None was a regular smoker and all had normal CT or 1.5 T MRI brain scans.…”
Section: Subjectsmentioning
confidence: 99%
“…The binding characteristics of some of the subjects have been previously published. 2,29,30 The subjects were clinically examined and were found to be free of psychiatric and neurologic disorders. None was a regular smoker and all had normal CT or 1.5 T MRI brain scans.…”
Section: Subjectsmentioning
confidence: 99%
“…Mukherjee et al (1995) could not detect specific receptor binding, when they extracted the main lipophilic metabolite of [ 18 F]fallypride from blood plasma of humans and incubated it in rat brain slices containing the striata. For determination of D 2 receptor occupancy, averaged BPs of control subjects were used as the common baseline value, based on the assumption that there is no difference in B max between patients and healthy control subjects when measured with benzamide radiotracers (Farde et al, 1987;Hietala et al, 1994). BP images were stereotactically normalized for calculation of D 2 /D 3 receptor occupancy.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…In vivo studies using radioligands which bind to post-synaptic dopamine receptors have provided equivocal evidence for abnormalities of striatal receptors. Some investigators have reported greater receptor density (Gjedde et al 1996;Wong et al 1986), whereas many groups have failed to replicate these findings (Farde et al 1990;Hietala et al 1994;Nordstrom et al 1995;Pilowsky et al 1994).…”
Section: Given Evidence For Excessive Striatal Dopamine Activity In Smentioning
confidence: 99%
“…In vivo studies using radioligands which bind to post-synaptic dopamine receptors have provided equivocal evidence for abnormalities of striatal receptors. Some investigators have reported greater receptor density (Gjedde et al 1996;Wong et al 1986), whereas many groups have failed to replicate these findings (Farde et al 1990;Hietala et al 1994;Nordstrom et al 1995;Pilowsky et al 1994).A more successful approach has been to measure the change in radioligand binding after the manipulation of synaptic dopamine concentration. Two groups have demonstrated that in response to amphetamine, patients with schizophrenia displace more dopamine D 2 -ligand than healthy subjects (Abi-Dargham et al 1998;Breier et al 1997;Laruelle et al 1996).…”
mentioning
confidence: 99%